2016
DOI: 10.1093/ajcp/aqw066
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Sulfate as an Alternative In Vitro Anticoagulant for the Measurement of Platelet Parameters?

Abstract: Magnesium anticoagulation might be advantageous for more reliable MPV measurements. Although platelet count is underestimated when the impedance method is used, the platelet count reveals similar results when measured by the fluorescent optical method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…The platelet counts, except in the heparin anti-coagulated samples, were similar, but, in contrast to the Na 2 EDTA and K 3 EDTA samples, the platelet counts in the citrate samples tended to decrease over time in some samples [19]. McShine and colleagues state that the MPV is around 6-13% lower in citrated samples as compared to the respective EDTA samples [55], which is in accordance with the observation of Dastjerdi et al, who show that the mean MPV measured from citrated samples was 0.66 fL (9%) lower than from the respective EDTA samples when measured within 1 h after sampling [56], and Mannuß et al, who found a difference of 1.32 fL (13.5%) after 180 min [8]. [58].…”
Section: Impact Of In Vitro Anticoagulation On Platelet Count and Mpvsupporting
confidence: 88%
See 1 more Smart Citation
“…The platelet counts, except in the heparin anti-coagulated samples, were similar, but, in contrast to the Na 2 EDTA and K 3 EDTA samples, the platelet counts in the citrate samples tended to decrease over time in some samples [19]. McShine and colleagues state that the MPV is around 6-13% lower in citrated samples as compared to the respective EDTA samples [55], which is in accordance with the observation of Dastjerdi et al, who show that the mean MPV measured from citrated samples was 0.66 fL (9%) lower than from the respective EDTA samples when measured within 1 h after sampling [56], and Mannuß et al, who found a difference of 1.32 fL (13.5%) after 180 min [8]. [58].…”
Section: Impact Of In Vitro Anticoagulation On Platelet Count and Mpvsupporting
confidence: 88%
“…After their detachment from megakaryocytes, platelets are the smallest cellular constituent of human blood. Under physiological conditions, their number is about 150,000 to 450,000 per μL of blood, and the mean platelet volume (MPV) is between 5 fL and 13 fL, depending on the applied method of measurement, the in vitro anticoagulant and the time delay between blood sampling and measurement [6,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, these methods do not agree with each other. Sample storage time is another parameter which influences MPV [75]. Although not all studies stated sample storage time in their investigation, MPV was significantly higher than controls in both ≤120 min and >120 min groups.…”
Section: Discussionmentioning
confidence: 86%
“…Mean platelet volume is routinely measured in blood samples anticoagulated with tripotassium-ethylenediaminetetraacetic acid (K3EDTA), collected for complete blood count. MPV increases in K3EDTA samples with time, due to platelet swelling [6][7][8][9][10][11] : As a consequence, the timing of MPV measurement after blood sampling should be standardized to allow accurate comparison of the values obtained in the same laboratory and across different laboratories. Lack of standardization of this important pre-analytical variable, in combination with different performances of hematology analyzers explain the wide interlaboratory variability of MPV normal ranges.…”
Section: In Vitro Variations Of Mean Platelet Volume Over Time In Blomentioning
confidence: 99%
“…8,12,13 With the aim of reducing the pre-analytical variability associated with K3EDTAinduced platelet swelling, anticoagulants different from K3EDTA have been tested and proposed as potentially useful for assessing platelet indices. 9,14 To identify the ideal pre-analytical variables for measuring MPV, we compared its variation over time in blood samples collected in 4 different anticoagulants from the same normal subjects and patients with inherited or acquired thrombocytopenias. The mean platelet count (±SD) was 252 × 10 9 /L (±64) in blood donors and 75 × 10 9 /L (±35) in thrombocytopenic subjects.…”
Section: In Vitro Variations Of Mean Platelet Volume Over Time In Blomentioning
confidence: 99%